Analisis Risiko Ergonomi Terhadap Gangguan Otot Rangka Akibat Kerja (GOTRAK) Pada Perawat Di Rumah Sakit Umum Haji Medan Tahun 2023 - Dwina, Idil Adriati; El-Matury, Herlina J.; Sitorus, Friska Ernita (Jurnal Kajian Kesehatan Masyarakat, 2023)
The majority of complaints involving the skeletal-muscle system are brought on by excessive muscle contraction as a result of exerting an excessive workload for an extended period of time. Ergonomics is the study of work harmony in a system. In its application, work will be safe for workers/humans and work efficiency will increase so that human welfare is achieved. Quantitative cross-sectional or cross-sectional research, or research that aims to examine the relationship between ergonomic risk (awkward posture, workload, duration and frequency) with work-related skeletal muscle disorders in nurses at the Hajj Generali Hospital, Medani City in 2023. The populace in this study were all nurses at Medan Hajj General Hospital. The Slovin formula was used in this study's sample selection, which resulted in 75 respondents. With a p value of 0.000, statistical tests performed with chi-square showed that awkward postures and work-related skeletal muscle disorders are related. There is also a relationship between workload and skeletal muscle disorders due to workp value of 0.009, there is a relationship between duration and skeletal muscle disorders due to work withp value of 0.018 and the relationship between frequency and skeletal muscle disorders due to work withp value of 0.000. It was discovered in the multivariate analysis that awkward postures and frequency were the dominant factors affecting skeletal-muscle disorders due to work in nurses at the Medan Hajj General Hospital in 2023, the value obtained p value of 0.000 with Odd Ratio 100.189 for awkward posture and p value of 0.045 with Odd Ratio of 8.237 for frequency. It is normal that nurses will actually want to apply work breaks or light extending for a couple of moments after carrying out repetitive activities for a long duration and for the directorate of Medan Hajj Hospital to pay more attention to and implement work stations with an ergonomic position. Keywords: Nurse, Ergonomic Risk, Work-related Skeletal Muscle Disorders